Social life cycle assessment in solar dryer house for postharvest loss management technology: Application of UNEP / SETAC in Tanzania - Mwaijande, Francis; Mkuna, Eliaza; Abeid , Ashiraf; Lyakurwa, Felichesmi; Sungau, Joseph; Manouchehr, Shokri (Arabian Journal of Business and Management Review (Kuwait Chapter), 2026)
A paper submmited to the Arabian Journal of Business and Management Review (Kuwait Chapter)